Integrated Activity Based Costing And Economic Value Added System Framework As A Financial Management Tool For Small And Medium Industries Using The SAAS Model - Sockanathan, Sivaneswaran (2010)
This system provides all these information for decision making. Using the Software as a Service (SaaS) model makes the system delivery affordable and provides cost effective service continuity for Small Medium Industries (SMI).